Heat sink design project - Dotson, Joshua; Cater, Ryan; Bai, Tian; Stein, Taylor; Steuber, Jason (Kansas State University. K-State Libraries, 2014)
A single phase, microchannel heat sink and an experiment to test the heat sink is designed. The heat sink is designed to cool a 30mm x 10 mm plate that is subjected to a constant heat flux of 500 W/cm^2, a maximum surface temperature of 80 *C, and a maximum pressure drop of 300 kPa. The final design uses 47 micrometer x 292 micrometer silicone channels. Finally, the design uses water at a mass flow rate of 41.657*10^-3 kg/s and a temperature rise of 8.6*C.
Kirmser Undergraduate Research Award - Group category, honorable mention
Citation: Dotson, J. (2014) Heat sink design project. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Microchannel; Heat sink; Mechanical engineering; Microfluidics